2014
DOI: 10.3906/bot-1405-26
|View full text |Cite
|
Sign up to set email alerts
|

Bucklandiella seppeltii, a new species of Grimmiaceae from Australasia, and its phylogenetic position based on molecular data

Abstract: A new species, Bucklandiella seppeltii Bednarek-Ochyra, Ochyra, Sawicki & Szczecińska, is delimited by its distinct morphology and biogeography. The geographical range of the new species is restricted to the southern-temperate and southern-cool-temperate zones of Tasmania and New Zealand, with maximum occurrence on the South Island of the latter insular country. The species is described and illustrated and its distribution is mapped. The systematic position of B. seppeltii is revealed to be a sister to New Zea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…(Ochyra et al, 2003). These studies have resulted in the discovery of some new species (Bednarek-Ochyra & Ochyra, 1996, 2011Bednarek-Ochyra et al, 2014), resurrection of some species from oblivion (Ellis et al, 2011;Bednarek-Ochyra, 2014) and new records of species previously known from elsewhere (Blockeel et al, 2008a;Ellis et al, 2014a, b). All of the species of Bucklandiella are known to occur on the South Island, while only four of them have so far been recorded in the North Island, including B. ptychophyllum (Mitt.)…”
Section: Bucklandiella Curiosissima (Bednarek-ochyra and Ochyra) Bednarmentioning
confidence: 99%
See 1 more Smart Citation
“…(Ochyra et al, 2003). These studies have resulted in the discovery of some new species (Bednarek-Ochyra & Ochyra, 1996, 2011Bednarek-Ochyra et al, 2014), resurrection of some species from oblivion (Ellis et al, 2011;Bednarek-Ochyra, 2014) and new records of species previously known from elsewhere (Blockeel et al, 2008a;Ellis et al, 2014a, b). All of the species of Bucklandiella are known to occur on the South Island, while only four of them have so far been recorded in the North Island, including B. ptychophyllum (Mitt.)…”
Section: Bucklandiella Curiosissima (Bednarek-ochyra and Ochyra) Bednarmentioning
confidence: 99%
“…All of the species of Bucklandiella are known to occur on the South Island, while only four of them have so far been recorded in the North Island, including B. ptychophyllum (Mitt.) Bednarek-Ochyra & Ochyra (Sainsbury, 1955), B. allanfifei Bednarek- , B. seppeltii Bednarek- Ochyra, Ochyra, Sawicki & Szczecińska (Bednarek-Ochyra et al, 2014), and B. chlorocarpa (Paris) Bednarek- Ochyra & Ochyra (Bednarek-Ochyra, 2014). This number is now increased by one species, B. curiosissima, which is the most distinctive and easiest to recognise from all other congeners.…”
Section: Bucklandiella Curiosissima (Bednarek-ochyra and Ochyra) Bednarmentioning
confidence: 99%
“…but it differs in having the apical portion of the calyptra densely papillose, epilose innermost perichaetial leaves and an entirely smooth, dextrorse seta (with the exception of one to several twists to the right immediately below the capsule and further down being twisted to the left in C. fascicularis). This taxonomic conclusion, based upon morphology, is well supported by phylogenomic analyses based upon complete platomes and mitogenomes, as well as nuclear rRNA gene clusters (Bednarek- Ochyra et al 2014;Sawicki et al 2015). Additionally, an analysis of nuclear ITS and plastid rps4-trnL and trnK/matK-psbA sequences (Larraín et al 2013) revealed the polyphyly of Codriophorus, which, accordingly, was split into two genera, including the monotypic Frisvollia Sawicki, Szczecińska, Bednarek-Ochyra & Ochyra and the oligotypic Dilutineuron Bednarek-Ochyra, Sawicki, Ochyra, Szczecińska & Plášek (BednarekOchyra et al 2015).…”
mentioning
confidence: 72%
“…These species are very distantly related and actually belong to two different genera which are characterised by suites of several structural traits. The former is recognised in the separate genus Niphotrichum Bednarek-Ochyra & Ochyra (Ochyra et al 2003;Bednarek-Ochyra et al 2014;Sawicki et al 2015), characterised by having, among other traits, prominent leaf auricles composed of large, hyaline, thinwalled and pellucid cells, laminal cells that are densely covered with tall conical papillae situated over the cell lumina, and papillose hyaline leaf hair-points.…”
mentioning
confidence: 99%
“…Thus, the present records of B. didyma on South Georgia complete its distribution in the Scotia Arc and bridge its Fuegian and Antarctic localities. Bucklandiella didyma is a panholantarctic species, which is also known from South Africa , SE Australia, Tasmania and New Zealand (Bednarek-Ochyra et al, 2014).…”
mentioning
confidence: 99%